Evaluation of Bomber Jackets Using Shaho Batik A Cultural Identity of Balikpapan East Kalimantan - Marthina Claudia Margaretha Sitohang; Eneng Lutfia Zahra; Rahayu Purnama (Journal of Creative Industries and Vocational Innovation, 2025)
This study aims to produce a bomber jacket using Shaho batik and to evaluate the aesthetic aspects of the bomber jacket made with Shaho batik from Balikpapan, East Kalimantan. This research employs a quantitative descriptive method with a pre-experimental research design in the form of a one-shot case study. As a result, five bomber jacket products were created using Shaho Batik and evaluated using a rating scale. The assessment instrument consisted of a questionnaire with 14 statements, measured using a rating scale, and was distributed to five expert panelists in the field. The aesthetic evaluation referred to three aspects: form or appearance, content or substance, and presentation or performance. Overall, the aesthetic evaluation achieved a score of 83.8%, classified as very good." For the form or appearance aspect, which includes design elements and principles, a score of 84.14% was obtained, categorized as "very good." The content or substance aspect, which includes ideas inspired by "Neo Culture Technology NCT Dream-Beatbox," received a score of 81.2%, also categorized as very good. Meanwhile, the presentation or performance aspect obtained a score of 84.8%, classified as very good. The product with the highest evaluation score was design number four, with a score of 88.8%, categorized as very good, while design number five received the lowest score of 76.8%, but still fell into the good category.